Seizure-Associated, Aberrant Neurogenesis in Adult Rats Characterized with Retrovirus-Mediated Cell Labeling - Jessberger, Sebastian (J Neurosci, 2007)
Seizure activity within the hippocampal circuitry not only affects pre-existing structures, but also dramatically increases the number of newborn granule cells. A retroviral strategy was used to label dividing cells and their progeny in the adult dentate gyrus and to analyze the impact of epileptic activity on adult-generated cells labeled before or after seizures. We show that epileptic activity led to dramatic changes in the neuronal polarity, migration, and integration pattern of newborn granule cells, depending on the time of birth in relation to the epileptic insult. Aberrant neurons were stably integrated into the dentate circuitry, and the consequences on hippocampal neurogenesis were long lasting. The data presented characterized the consequences of seizure-associated plasticity on adult neurogenesis leading to long-term structural changes in the hippocampal circuitry that might represent a pivotal component of the epileptic disease process.